Biopharmaceutical and nanotoxicological aspects of cyclodextrins for non-invasive topical treatments: A critical review - Riccio, Bruno Vincenzo Fiod [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Baveloni, Franciele Garcia [UNESP]; de Antoni, Juliana Aenishanslin; Robusti, Leda Maria Gorla [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Ferrari, Priscileila Colerato; Chorilli, Marlus [UNESP] (Wiley, 2022)
Cyclodextrins are nanometric cyclic oligosaccharides with amphiphilic characteristics that increase the stability of drugs in pharmaceutical forms and bioavailability, in addition to protecting them against oxidation and UV radiation. Some of their characteristics are low toxicity, biodegradability, and biocompatibility. They are divided into α-, β-, and γ-cyclodextrins, each with its own particularities. They can undergo surface modifications to improve their performances. Furthermore, their drug inclusion complexes can be made by various methods, including lyophilization, spray drying, magnetic stirring, kneading, and others. Cyclodextrins can solve several problems in drug stability when incorporated into dosage forms (including tablets, gels, films, nanoparticles, and suppositories) and allow better topical biological effects of drugs at administration sites such as skin, eyeballs, and oral, nasal, vaginal, and rectal cavities. However, as they are nanostructured systems and some of them can cause mild toxicity depending on the application site, they must be evaluated for their nanotoxicology and nanosafety aspects. Moreover, there is evidence that they can cause severe ototoxicity, killing cells from the ear canal even when applied by other administration routes. Therefore, they should be avoided in otologic administration and should have their permeation/penetration profiles and the in vivo hearing system integrity evaluated to certify that they will be safe and will not cause hearing loss.
Keywords: drug dosages; nanotoxicology; ototoxicity; stability; structural modifications